Choosing a map projection - Lapaine, Miljenko; Usery, E. Lynn 1951- (Springer, 2017)
This book offers a much-needed critical approach to the intelligent use of the wide variety of map projections that are rapidly and inexpensively available today. It also discusses the distortions that are immanent in any map projection. A well-chosen map projection is one in which extreme distortions are smaller than those in any other projection used to map the same area and in which the map properties match its purpose. Written by leading experts in the field, including W. Tobler, F.C. Kessler, S.E. Battersby, M.P. Finn, K.C. Clarke, V.S. Tikunov, H. Hargitai, B. Jenny and N. Frančula. This book is designed for use by laymen. The book editors are M. Lapaine and E.L. Usery, Chair and Vice-Chair, respectively, of the ICA Commission on Map Projections for the period 2011-2015.
Keywords: Map projection.; elektronické knihy; electronic books